An Effective Model for Analysis Web User’s Behavior from Web Log Data - Mehra, Jayanti; R.S. Thakur, Dr. (International Journal of Engineering and Technology, 2018)
The regular explosion of e-Commerce, there is strong competition amongst companies and other sectors to be a focus for the customers. Web server analysis is very difficult to find out the web user behavior for any organization. It is useful for future web site improvement and design. In this paper, has to propose a PDFCM-based approach for assigning weights to client sessions for considering the high dimensionality of client session information. To analyzing the client session cluster, we use fuzzy c-means (FCM) algorithm. A major challenge for these methods is selection of suitable cluster center, so it has to propose PDFCM-based algorithm to solve this problem. Clustering is also used to approximation the number of clusters this clustering is similarly used to calculate the number of clusters. Our outcomes demonstrate that the quality of the clusters framed utilizing the proposed algorithm is much superior. So, outcome shows our proposed methodology is much batter then the other algorithms.Â Â